The role of ω in the precipitation of α in near-β Ti alloys. (May 2016) - Li, Tong; Kent, Damon; Sha, Gang; Cairney, Julie M.; Dargusch, Matthew S.
Abstract: To identify the conditions under which ɷ assists α formation in a near-β Ti alloy, we employed transmission electron microscopy and atom probe tomography to study α precipitation in alloys designed to contain two different types of ɷ. Coherent incommensurate embryonic ɷ formed upon isothermal ageing, does not directly assist α precipitation. When this incommensurate embryonic ɷ grows to a critical size, it transforms into commensurate isothermal ɷ, during which stress is thought to be the dominant factor. Regions of O enrichment at the semi-coherent isothermal ɷ/β interfaces are observed, which is thought to promote α formation. Graphical abstract: